Online Learning Methods With Stress Of Parents With Children Ages 7-9 Years In The COVID-19 Pandemic Season - Dina Zakiyatul Fuadah; Andika Siswoaribowo (Chakra Brahmanda Lentera Institute, 2022)
Background: The 2019 ongoing coronavirus disease around the world. One of the impacts is in the field of education. As a result, the learning process is carried out at home through online/distance learning. This study aimed to determine the relationship between online learning methods and the stress level of parents of children aged 7-9 years in the COVID-19 pandemic season at MI Da'watul Khoiriyah, Nambakan Hamlet, Ringinrejo District. Methods: This research design is cross-sectional. The sample size is 37 respondents using purposive sampling. Data were analyzed using a nonparametric test in Spearman's nonparametric Statistic Test. Based on the study's results, it was found that most of the respondents (70.8%), as many as 26 online learning had good categories Results: Meanwhile, almost half of the respondents (48.6%), as many as 18 stress levels of parents of children have a mild stress category. The results of the Spearman's Rho Nonparametric statistical test obtained a p-value: 0.005 (a < 0.05) with r = 0.457 (sufficient intensity) with a positive direction, meaning that there is a relationship between online learning and the stress level of parents of children during the Covid-19 pandemic season in MI Da' Watul Khoiriyah Dusun Nambakan Ringinrejo. Conclusion: It is recommended that parents be able to reduce stress on themselves, make the right decisions, and build exemplary communication with their children to improve children's learning at home